Polyphosphate synthesis is an evolutionarily ancient phosphorus storage strategy in microalgae - Cliff A; Guieysse B; Brown N; Lockhart P; Dubreucq E; Plouviez M (Elsevier B.V., 2023)
To assess the ubiquity of the potential for inorganic polyphosphate (polyP) synthesis in microalgae, we searched databases for algal homologues to the polyP polymerase VTC4 of Chlamydomonas reinhardtii. Homologues of this protein were found within >40 species of microalgae known to inhabit marine, freshwater, and terrestrial environments. Phylogenetic analysis demonstrated that these proteins were organized into clades aligning with their taxonomic relationships. These similarities and evolutionary relationships suggest that polyP synthesis represents an ancient ability that has evolved with species as the microalgal lineage has spread out over time. Based on these results and prior knowledge on P metabolism, C. reinhardtii, Chlorella vulgaris, Desmodesmus cf. armatus, Gonium pectorale, and Microcystis aeruginosa were further tested in bioassays known to trigger the synthesis of polyP within dense granules, by addition of P following a period of P depletion. While the cellular P content of C. reinhardtii, G. pectorale, M. aeruginosa, and D. cf. armatus increased to similar maxima, ranging from 2.6 ± 0.5 % to 3.6 ± 1.3 % 24 h after P repletion, P content only reached 1.2 ± 0.2 % in C. vulgaris, suggesting a lesser ability to accumulate polyP than the strains of the other species. Models of predicted VTC4 proteins were generated from the four eukaryotic species tested and showed that the microalgae share the conserved VTC catalytic core and SPX phosphate-sensing domains found in the yeast VTC4 proteins. This confirms the role of microalgal VTC4 as polyP polymerase and suggests a similar regulation of VTC4 proteins to the one described in yeast. Further work is now needed to uncover the assembly of the microalgal VTC complex and its regulation. A deeper study of the microalgal VTC structure could also help to understand whether differences in VTC structures can explain observed differences in P accumulation kinetics.
Keywords: Polyphosphate; Chlamydomonas; Phylogeny; VTC4; Protein models; Protein homology; AlphaFold